Testy plasujące jako narzędzie pomiaru dydaktycznego na prz ykładzie jęz yka polskiego jako obcego – ocena dotychczasowych doświadczeń - Lipińska, Ewa (Neofilolog, 2010)
The placement test is a special examination used to test students’ language proficiency so that they may be placed in an appropriate course. It should be relatively short, yet comprehensive. The test used in the Jagiellonian University Center for Polish Language and Culture in the World has been based on the standards set in two documents, namely the Common European Framework of Reference (2001) and the Polish Language Proficiency Standards (2003). It consists of 2 parts – written and oral. In the written part it concentrates on assessing students’ knowledge of grammar and vocabulary, as well as reading and writing abilities. The oral part assesses students’ productive and interactive skills. The article presents all the development stages of the placement test and its subsequent modifications. It also discusses the choice of testing tasks and the means of evaluating students’ production.